Reconfiguração de redes de distribuição considerando multivariáveis e geração distribuída - Mello, Ana Paula Carboni de (2014)
The new design of electric power system, called Smart Grid, has emerged as a new challenge especially for power distribution networks, which need to promote greater functionality such as real-time monitoring of the information about the energy consumption of consumers, the massive automation with smarter equipment and devices, monitoring and quick action when facing problems, connection of distributed generation, among others. The connection of distributed generation sources such as wind and solar power in the distribution network is becoming an increasingly common practice and it has great influence on several aspects of the distribution network, especially in system reconfiguration. The initial topology of the feeders may not be ideal after the connection of the power generation, as well as the power flow is modified by the distributed generation. In this sense, this Master Thesis presents a methodology for the management of distribution networks through reconfiguration of the network topology and the power injection of distributed generators based on wind, photovoltaic and hydroelectric generation. The solution of the reconfiguration problem is based on heuristic technique Branch Exchange, which seeks to optimize multiple objectives. To select the networks configuration the multi-criteria decision AHP (Analytic Hierarchy Process) method is used. To illustrate the efficiency of the methodology the results for a real network of an electric utility are presented, considering different scenarios of load and distributed generation availability, as well as validation of the results by the exhaustive search method.